2015
DOI: 10.1515/pjct-2015-0016
|View full text |Cite
|
Sign up to set email alerts
|

Effect of magnetic field and silver nanoparticles on yield and water use efficiency of Carum copticum under water stress conditions

Abstract: Normally the productivity of cropping systems in arid and semi-arid regions is very low. The sustainable agricultural systems try to fi nd out environmental friendly technologies based on physical and biological treatments to increase crop production. In this study two irrigation treatments (control and water stress) and six methods of fertilizer treatment (control, NPK-F, using magnetic band-M, using silver nano particles-N, M+N and M+N+50% F) on performance of ajowan were compared. Results showed that treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(5 citation statements)
references
References 32 publications
0
4
0
1
Order By: Relevance
“…Therefore, nanotechnology such as using nanoscale fertilizer may offer new techniques to be used for crop management. The efficient use of nano-scale microelements was reported by many authors including titanium (Hasanpour et al 2015;Singh and Lee 2016;Tan et al 2017) silicon (Siddiqui et al 2014;Ashkavand et al 2015;Sabaghnia and Janmohammadi 2015;Qados and Moftah 2015;Liu et al 2015;Wang et al 2015;Mahdavi et al 2016) silver (Seghatoleslami et al 2015;Almutairi 2016) iron (Martínez-Fernández et al 2015;Pourjafar et al 2016) zinc (Seghatoleslami and Forutani 2015;Soliman et al 2015). The previous reports also described the role of nanomaterials in ameliorating biotic stress in plant habitat.…”
Section: Nanobiotechnology For Crop Productivitymentioning
confidence: 94%
“…Therefore, nanotechnology such as using nanoscale fertilizer may offer new techniques to be used for crop management. The efficient use of nano-scale microelements was reported by many authors including titanium (Hasanpour et al 2015;Singh and Lee 2016;Tan et al 2017) silicon (Siddiqui et al 2014;Ashkavand et al 2015;Sabaghnia and Janmohammadi 2015;Qados and Moftah 2015;Liu et al 2015;Wang et al 2015;Mahdavi et al 2016) silver (Seghatoleslami et al 2015;Almutairi 2016) iron (Martínez-Fernández et al 2015;Pourjafar et al 2016) zinc (Seghatoleslami and Forutani 2015;Soliman et al 2015). The previous reports also described the role of nanomaterials in ameliorating biotic stress in plant habitat.…”
Section: Nanobiotechnology For Crop Productivitymentioning
confidence: 94%
“…NPs may be directly involved in the elimination of ROS, which reduces the levels of antioxidant enzymes. Seghatoleslami et al (2015) reported the effects of Ag NPs on the yields and WUE of drought-stressed Carum copticum using a magnetic field.…”
Section: Examples Of Nps and The Roles They Play In Relieving Stress ...mentioning
confidence: 99%
“…The effects of seeds irrigated with magnetically treated water showed an increase in root length, plant height, number of leaves, number of branches, fresh and dry weight at the three irrigation levels (80, 60, 40%) concerning the control groups. Inversely, Seghatoleslami et al (2015) demonstrated that water stress and 10 mT of B field stimulation used 30 × 10 mm magnetic strips as a pre-sowing treatment of ajwain (Carum copticum) does not generate any significant effect on plant development. However, it does promote an increase in nutrient uptake in plants.…”
Section: Guo Et Al (2017)mentioning
confidence: 99%